2012
DOI: 10.1007/s00418-012-1059-4
|View full text |Cite
|
Sign up to set email alerts
|

Golgi fragmentation is Rab and SNARE dependent in cellular models of Parkinson’s disease

Abstract: Fragmentation of the Golgi ribbon is a common feature of many neurodegenerative diseases but little is known about the causes of this alteration. In Parkinson's disease, it is believed to be the consequence of an ER-Golgi transport imbalance and/or of cytoskeleton alterations. In the present study, we analyze the mechanisms involved in Golgi fragmentation in differentiated PC12 cells treated with 6-hydroxydopamine or methamphetamine as cellular models of Parkinson's disease. Our data demonstrate that Golgi fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 35 publications
7
64
0
Order By: Relevance
“…Re-expression of Rab8B SR or Rab29 SR in the respective knockdown cells, however, did not restore the compacted Golgi at all (Fig. 3, A and B) despite the fact that involvement of Rab8 and Rab29 in Golgi morphology had been reported by other groups (15,17). The Rab8B and Rab29 siRNAs used in this study may also reduce the expression level of some other unrelated molecule(s) that is required for the compacted Golgi morphology.…”
Section: Resultsmentioning
confidence: 54%
“…Re-expression of Rab8B SR or Rab29 SR in the respective knockdown cells, however, did not restore the compacted Golgi at all (Fig. 3, A and B) despite the fact that involvement of Rab8 and Rab29 in Golgi morphology had been reported by other groups (15,17). The Rab8B and Rab29 siRNAs used in this study may also reduce the expression level of some other unrelated molecule(s) that is required for the compacted Golgi morphology.…”
Section: Resultsmentioning
confidence: 54%
“…The Rab GTPase Rab8a, which showed the strongest rescue of αS-toxicity in the nematode PD model (Gitler et al, 2008), is associated with recycling endosomes and basolateral trafficking events from the trans-Golgi network to the plasma membrane (Henry and Sheff, 2008). Also, Golgi fragmentation was recently shown to be Rab and SNARE dependent in cellular models of PD, further linking Rab8 with αS (Rendon et al, 2013). Although the genetic variant A30P αS has been observed to co-precipitate with Rab8 in transgenic mice (Dalfo et al, 2004b), no direct interaction between Rab8a, or any other Rab GTPase, with αS has been reported thus far.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a single amino acid substitution of a phosphorylated residue on the yeast homologue Sed5 resulted in the normally dispersed yeast Golgi apparatus to form an ordered structure similar to the mammalian Golgi apparatus (21). Interestingly, another study showed that STX5 levels affected Golgi apparatus order in the presence of a drug that fragments the Golgi apparatus (22). STX5 is also linked to rebuilding Golgi apparatus morphology following mitosis.…”
Section: Discussionmentioning
confidence: 99%